Implementation Of Strategic Management To Enhance Educational Quality: A Perspective Of Postgraduate Students At Malang State Islamic University - Bulqis, Bulqis; Abidin, Munirul (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The purpose of this research is to find information about the implementation of strategic management to enhance the quality of education from the perspective of postgraduate students at Malang State Islamic University. The research method used is descriptive qualitative research with a case study design. Data collection techniques in the form of interviews with the form of unstructured interviews. The research subjects are postgraduate students in Islamic education management of Malang State Islamic University, selected based on criteria such as having work experience in the field of education, such as curriculum vice principals, student affairs vice principals, and educators. Subsequently, data analysis is conducted through a series of coding processes and categorization according to theories related to strategic management. The research findings indicate that in the implementation of strategic management to enhance the quality of education, there are several elements, including environmental observation, strategy formulation, strategy implementation, and evaluation. Additionally, there are inhibiting factors and supporting factors in implementing strategic management. Improving the quality of education is not solely focused on academic outcomes but also involves effective, organized management that is synergistic towards all aspects supporting the enhancement of education quality.   Keywords: Implementation, Strategy Management, Education Quality